Communicative patterns in online health communities: A comparative study of Italian and Polish - Bongelli, Ramona; Tereszkiewicz, Anna; Paolanti, Marina; Riccioni, Ilaria (PloS one, 2025)
This paper explores how online health platforms influence communication between patients and healthcare professionals, focusing on anxiety-related interactions in Italy and Poland. The study examines pairs of questions and answers, selected from Q&A services, within MioDottore and ZnanyLekarz , two medical platforms operating in these countries, with the main aim of identifying cross-cultural similarities and differences in communication strategies. Anxiety was chosen as a case study because it is one of the most prevalent mental health conditions, as revealed by research and national statistics, and because it is a prominent topic of discussion within online medical communities. Italy and Poland were chosen for comparison because of their different linguistic and socio-cultural contexts. Data were collected through an automated process based on a web-scraping algorithm and analysed using a mixed methods approach combining quantitative and qualitative techniques. The results show some clear differences in communicative patterns: Italian patients tend to use more indirect and polite forms, while Polish patients use a more direct style. Among practitioners, gender-related differences were found in the Polish responses: Polish women tend to adopt a more emphatic style. By contrast, Italian responses seem to be more influenced by professional specialisation: while psychiatrists tend to adopt a more pragmatic style (focusing more on the informational and request-oriented aspects of users’ posts), psychologists typically adopt a more empathic approach (paying more attention to the emotional dimension, often linked to the suffering experiences disclosed by users). These findings highlight how digital health communication reflects broader cultural and professional norms, although further research is needed to confirm these patterns across different conditions and clinical settings.